Assessment of executive functioning in children and young adults treated for frontal lobe tumours using ecologically valid tests. Issue 4 (3rd July 2016) - Longaud-Valès, A.; Chevignard, M.; Dufour, C.; Grill, J.; Puget, S.; Sainte-Rose, C.; Valteau-Couanet, D.; Dellatolas, G.
Abstract : There is a lack of studies assessing executive functions (EF) using ecologically valid tests in children with frontal lobe lesions. This study aimed to (1) evaluate EF in children, adolescents and young adults treated for childhood frontal lobe tumours, (2) identify factors influencing performance, such as age at diagnosis or type of treatment, and (3) examine correlations between intellectual ability and classical and ecological tests of EF. Twenty-one patients, aged 8–27 years, treated for a childhood benign or malignant frontal lobe tumour, and 42 healthy controls (matched for gender, age and socio-economic status) were assessed using classical tests of EF, and the BADS-C ecological battery. Patients also underwent assessment of intellectual ability and parent and teacher ratings of the BRIEF questionnaire. IQ scores ranged from 45 to 125 (mean FSIQ = 84) and were lower in case of epilepsy, hydrocephalus and lower parental education. Patients displayed deficits in most, but not all measures of EF. Most classical and ecological measures of EF were strongly correlated to IQ. This study confirms the frequency of EF deficits in this population; it also highlights the utility of ecological measures of EF and some limitations of classical tests of EF in children.